Impact of Pharmacogenetic Markers of CYP2D6 and DRD2 on Prolactin Response in Risperidone-Treated Thai Children and Adolescents With Autism Spectrum Disorders. Issue 2 (April 2016) - Sukasem, Chonlaphat; Hongkaew, Yaowaluck; Ngamsamut, Nattawat; Puangpetch, Apichaya; Vanwong, Natchaya; Chamnanphon, Montri; Chamkrachchangpada, Bhunnada; Sinrachatanant, Ananya; Limsila, Penkhae
Abstract : Objective: The aim of the study was to identify the impact of pharmacogenetic markers associated with prolactin concentration in risperidone-treated children and adolescents with autism spectrum disorders. Methods: One hundred forty-seven children and adolescents with autism, aged 3 to 19 years, received risperidone. The clinical data of patients were recorded from medical records. Prolactin levels were measured by chemiluminescence immunoassay. Three CYP2D6 single nucleotide polymorphisms, CYP2D6*4 (1846G>A), *10 (100C>T), and *41 (2988G>A), 1 gene deletion (*5 ), and DRD2 Taq1A (rs1800497) polymorphism were genotyped by TaqMan real-time polymerase chain reaction. Results: The 3 common allelic frequencies were CYP2D6 *10 (55.10%), *1 (32.65%), and *5 (6.12%), respectively. Patients were grouped according to their CYP2D6 genotypes. There was no significant correlation between the concentrations of prolactin among the CYP2D6 genotypes. In addition, there were no statistical differences in the prolactin response among the CYP2D6 -predicted phenotypes of extensive metabolizer and intermediate metabolizer. The DRD2 genotype frequencies were Taq1A A2A2 (38.77%), A1A2 (41.50%), and A1A1 (19.73%), respectively. There were statistically significant differences in prolactin level of patients among the 3 groups ( P = 0.033). The median prolactin level in patients with DRD2 Taq1A A2A2 (17.80 ng/mL) was significantly higher than A1A2 (17.10 ng/mL) and A1A1 (12.70 ng/mL). Conclusions: DRD2 Taq1A A2A2 polymorphisms may play a significant role in the hyperprolactinemia- associated with risperidone treatment in children and adolescent with autism spectrum disorder. Many drugs used chronically in psychiatric diseases exert their effects mainly through the dopamine D2 receptor. It is therefore possible that these drugs could alter the expression of any dopamine receptor, thus affecting the pharmacodynamics characteristics and toxicity of drug substrates during pharmacotherapy.